Analisis Iklim Organisasi Pada Yayasan Cahaya Bagi Negeri Di Cikarang - Lumbanbatu, Citra; Tamba, Rousdy Safari (JAMBIS : Jurnal Administrasi Bisnis, 2024)
The Cahaya Bagi Negeri Foundation exemplifies effective organizational practices, including clear structures, supportive work cultures, and robust conflict management systems. However, continuous efforts are needed to enhance employee engagement and commitment through performance evaluations and feedback mechanisms. The study concludes that organizational climate significantly influences employee performance, emphasizing the importance of effective communication, managerial support, and employee involvement in decision-making. The foundation must maintain a positive organizational climate by enhancing training programs, internal communication, and work facilities to achieve organizational goals while ensuring employee well-being and job satisfaction.